2000
DOI: 10.1152/ajpregu.2000.278.3.r628
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+-induced endothelium-dependent relaxation of blood vessels and blood pressure lowering: role of NO

Abstract: In vitro extracellular Mg(2+) concentration ([Mg(2+)](0)) produces endothelium-dependent and endothelium-independent relaxations in rat aorta in a concentration-dependent manner. These relaxant effects of Mg(2+) on intact rat aortic rings, but not denuded rat aortic rings, were suppressed by either N(G)-monomethyl-L-arginine (L-NMMA), N(omega)-nitro-L-arginine methyl ester (L-NAME), or methylene blue. The inhibitory effects of L-NMMA and L-NAME could be reversed partly by L-arginine. [Mg(2+)](0)-induced dilata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 29 publications
7
57
0
1
Order By: Relevance
“…Indeed, cellular depletion of K i and Mg i is associated with elevated blood lipid levels, atherosclerosis, 32 altered endothelial function, and decreased biosynthesis and release of NO. 33 Second, the coordinate nature of these cellular ionic lesions-ie, abnormal levels of any 1 ion reflecting linked abnormalities of others-suggests the somewhat artificial nature of controversies arising out of claims that 1 particular cellular ionic species is more important than another. It may be rather, that independently of the nature of the initial lesion, which might differ in different genetically or environmentally determined forms of hypertension and/or diabetes (and which may or may not involve primary ion-related events), that the alterations of cellular ion content observed here participate in a final common pathway necessary for the emergence of the insulin resistant and/or hypertensive state.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cellular depletion of K i and Mg i is associated with elevated blood lipid levels, atherosclerosis, 32 altered endothelial function, and decreased biosynthesis and release of NO. 33 Second, the coordinate nature of these cellular ionic lesions-ie, abnormal levels of any 1 ion reflecting linked abnormalities of others-suggests the somewhat artificial nature of controversies arising out of claims that 1 particular cellular ionic species is more important than another. It may be rather, that independently of the nature of the initial lesion, which might differ in different genetically or environmentally determined forms of hypertension and/or diabetes (and which may or may not involve primary ion-related events), that the alterations of cellular ion content observed here participate in a final common pathway necessary for the emergence of the insulin resistant and/or hypertensive state.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] Magnesium, a known vasodilator with anti-inflammatory effects, has the potential to alter the pathophysiology of pain crises. [16][17][18][19][20] In addition to work exploring the use of magnesium administered orally to prevent pain crises, 21,22 2 previous single-institution studies examining the effects of IV magnesium on acute pain crisis yielded conflicting results: one showed a shortened length of stay (LOS) from a median of 5 days to a median of 3 days compared with previous hospitalizations by the same individuals. Conversely, a randomized trial conducted in Canada with 104 children and an average LOS of more than 5 days found no decrease in length of hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium therapy may also improve endothelial function [12,13]. In addition to reverse interaction with ET-1, magnesium induces endothelium-dependent vasodilation mediated by endothelial NO [9,10]. NO, derived from nitric oxide synthase-3 in vascular endothelium, contributes to regulation of local circulatory disturbances, and may be neuroprotective by causing vasodilation and increased blood flow in the glaucoma patients [59,60].…”
Section: Putative Therapeutic Effect In Glaucomamentioning
confidence: 99%
“…Elevated magnesium levels prevents ET-1 induced contractile responses by inhibition of ET-1's production and its hypertrophic effect [7,8]. Endothelium-dependent vasodilation mediated by NO is induced with magnesium by modifying formation and release of NO [9][10][11]. Indeed, magnesium therapy may improve endothelial function in patients with diabetes and coronary artery diseases [12,13].…”
Section: Introductionmentioning
confidence: 99%